2018
DOI: 10.1002/jcp.27112
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of CLEC14A is associated with its expression and lung adenocarcinoma progression

Abstract: Our main objective is probing the effect of methylation of CLEC14A on its expression and lung adenocarcinoma (LUAD) progression. Microarray analysis was utilized to screen out differentially downregulated genes with hypermethylation in LUAD tissues. The CLEC14A expression level was measured by western blot analysis and qRT-PCR. Methylation-specific-PCR was performed to evaluate methylation status of CLEC14A. The 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromid (MTT) assay was used to check the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Simmilary, in non-small lung cancer, high ROBO4 tissue expression was related to good prognosis and was connected with normalization of endothelial cells and reduction of cancer spread [16]. Considering CLEC14A, recent reports indicate that elevated levels of this molecule can inhibit carcinogenesis and progression of lung adenocarcinoma [35]. The expression of ROBO4 or CLEC14A molecules in various cancers tissues (up-or down-regulation) suggests that these proteins may act as important modulators of tumorgenesis and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Simmilary, in non-small lung cancer, high ROBO4 tissue expression was related to good prognosis and was connected with normalization of endothelial cells and reduction of cancer spread [16]. Considering CLEC14A, recent reports indicate that elevated levels of this molecule can inhibit carcinogenesis and progression of lung adenocarcinoma [35]. The expression of ROBO4 or CLEC14A molecules in various cancers tissues (up-or down-regulation) suggests that these proteins may act as important modulators of tumorgenesis and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Simmilary, in nonsmall lung cancer, high ROBO4 tissue expression was related to good prognosis and was connected with normalization of endothelial cells and reduction of cancer spread [16]. Considering CLEC14A, recent reports indicate that elevated levels of this molecule can inhibit carcinogenesis and progression of lung adenocarcinoma [35]. The expression of ROBO4 or CLEC14A molecules in various cancers tissues (up-or down-regulation) suggests that these proteins may act as important modulators of tumorgenesis and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, high expression of CLEC14A in this cancer type correlated with improved clinical outcomes. A further study indicated that the methylation status of CLEC14A strongly correlated with its expression levels in NSCLC, and CLEC14A protein levels were reduced in tumour tissues compared to healthy adjacent tissue . Similar to CD93, CLEC14A was described as a key gene in a proposed ‘tumour angiogenesis signature’ determined by meta‐analysis of over 1000 tumour samples including breast, renal and head and neck cancers .…”
Section: Clec14amentioning
confidence: 93%
“…CLEC14A expression has been demonstrated in two different human lung cancer cell lines in vitro and when CLEC14A was further overexpressed in these cell lines, this led to reductions in proliferation, migration and invasion as well as reductions of in vivo tumour formation as xenografts in nude mice . However, the physiological relevance of CLEC14A expression in tumour cells themselves remains to be seen as such expression has not been reported in clinical specimens or in tumour cells by any other group.…”
Section: Clec14a Expressionmentioning
confidence: 99%